Petsitter: A mobile application for petsitter finder in Shah Alam / Noor Arissa Mohd Hariri - Mohd Hariri, Noor Arissa (2021)
The thriving of the economy these days has made it slightly harder for the worker to spend their time at home because they are becoming busier and busier. Therefore, a good technology is needed to cater to their responsibility as they need to focus on their works the most. This project is about the development of pet sitter finder around Seksyen 7 Shah Alam and the reason of developing this project is to assist the users to find the pet sitters around them as well as contacting the sitters all through their fingertips. Several problems of this project are the lack of medium for these pet owners to search for the pet sitters as well as to navigate to the location. These users also having difficulty to book for a service because usually they need to go or ask someone to go to the pet shops for service’s booking. So, this project is useful for pet sitter finder. The objective of this project is to determine user requirement, to design and to develop PetSitter finder mobile application. The scope of this project are the community of Seksyen 7 Shah Alam. However, the limitation of this project is it does not offer system booking, meaning the user need to contact the sitter through their email and pay manually since there will be no payment gateway available in this application. Users can view other available and registered users as well to start chatting for any inquiries. Meanwhile, all users have access to post and advertise their service if they can be pet sitter. Methodology that had been used for this project is Mobile Application Development Life Cycle (MADLC) Model. This project however will be developing up until testing phase only. The outcome that can be concluded based on the result show that the users will have more options to find the suitable pet sitters for them as well as the way to navigate to the location. Therefore, users generally who are searching for pet sitters and user who can be the pet sitters, as well as mobile application technologist are the significance of this project. For future direction, it is recommended to include booking system and online payment for faster transactions. The function of rating and review also can be made to give better impression towards the services.